Tradução, adaptação cultural e validação do instrumento Trajectory Complexity Assessment Tool (TRACT) de mensuração da carga de trabalho de enfermagem para o português brasileiro - Ângela Maria Rodrigues dos Santos (2021)
New instruments have been developed to assist nurses in assessing and measuring the nursing workload. The Trajectory Complexity Assessment Tool (TRACT), developed by Professor Davina Allen of Cardiff University, describes and evaluates the organizational components of nursing work based on the professional judgment of nurses. It is designed to assess and measure the volume and complexity of these components in patient care and the nursing workload. It comprises ten factors evaluated in 5 levels of complexity ranging from very low to very high. Aim: To culturally adapt and validate the content of the TRACT instrument designed to measure nursing workload. Method: This methodological study addressed the translation, cultural adaptation, and content validation of the TRACT. First, the translation of TRACT was carried out in partnership with the Experimental Translation Laboratory of the School of Languages of the Federal University of Minas Gerais. The initial translation, synthesis of the translations, and back-translation into the original language were performed. After this step, the translated version, which reached consensus among the researchers and the original excerpt of the instrument, were submitted for evaluation by a Committee of Judges through the digital platform Google Forms. This committee comprised 21 health professionals in cycle 1 for the first translation evaluation and 15 in cycle 2 for the second evaluation. The inclusion criterion for the judges' committee was to pursue experience with cultural adaptation and validation of instruments and/or with the use of instruments to measure nursing workload. In order to evaluate the agreement between the judges, the Content Validity Index (CVI) of each item and the overall CVI were calculated, and only indexes higher than 0.90 were considered valid. Results: In the instrument translation phase, meetings were held between the translators and the researchers for adjustments and consensus about the version, which the Judges Committee would evaluate. The judges were health professionals who worked in the areas of teaching (57.1%) and management (42.1%) and had their highest levels of education as PhD (71.4%), Master's degree (14.3%), and postgraduation (14.3%). The TRACT showed good acceptance among the judges, and in the first cycle, the lowest CVI per item obtained was 0.762, and the highest was 0.952. The following four items were sent for being reassessed in the second cycle - 'Care team' (0.762), 'Resources' (0.857), 'Interventions and Procedures' (0.857) and 'Assessment level' (0.857). In the second cycle, the lowest CVI was 0.905, and the highest was 1.0, with the overall CVI of the TRACT instrument reaching 0.934. Conclusion: The translation and cultural adaptation of the TRACT into Brazilian Portuguese provides a new tool for measuring workload in nursing that was considered valid for the Brazilian hospital context. As technical products of this study, the TRACT and its User's Guide were made available in Brazilian Portuguese for application by the nursing professionals at the time of patient assessment.